Do ditch‐side electric fences improve the breeding productivity of ground‐nesting waders?. Issue 2 (27th April 2022) - Verhoeven, Mo A.; Jelle Loonstra, A. H.; Pringle, Thomas; Kaspersma, Wiebe; Whiffin, Mark; McBride, Alice D.; Sjoerdsma, Pieter; Roodhart, Celine; Burgess, Malcolm D.; Piersma, Theunis; Smart, Jennifer
Abstract: Insufficient reproduction as a consequence of predation on eggs and chicks is a major determinant of population decline in ground‐nesting birds, including waders. For many populations, there is an urgent need to maintain breeding populations at key sites, and conservation practitioners need to find viable management solutions to reduce predation. One tool available to the practitioner is fences that exclude key predators from areas containing breeding birds. Temporary electric fencing is an increasingly popular predator exclusion intervention, but such fences have costs associated with purchase and the time needed to erect and maintain them. Their effectiveness and optimal application are also frequently questioned. We evaluate the use of temporary ditch‐side four‐strand electric fences in lowland grasslands in two countries, The Netherlands and England, in areas containing high densities of breeding waders. In both countries and in all years, godwit and lapwing nest survival was significantly higher within areas enclosed by ditch‐side electric fences. Brood survival, assessed for godwits in The Netherlands, was also higher within fenced areas in all years. This demonstrates that using temporary electric fences to enclose ground‐nesting birds can be an effective tool for improving breeding productivity. In our study, closely managed electric fences were effective at excluding red foxes Vulpes vulpes, but not avian and other mammalian predators. The positive effect that electric fencing had on nest and brood survival therefore likely results from a reduction in the total number of visits by mammalian predators, and especially visits by foxes. Although it requires a substantial time investment throughout the period of use, our temporary electric fence design provides flexibility compared to other fence designs when it comes to enclosing different areas within a season and between years, as the targets for protection change or as land and flood management dictate. This conservation intervention can help buy the time required to develop and implement longer term solutions for application at larger scales. Abstract : Our spatially and temporally replicated study shows that temporary ditch‐side electric fencing in lowland grasslands can be a successful conservation intervention for improving wader productivity.